2004
DOI: 10.1080/0263514042000290877
|View full text |Cite
|
Sign up to set email alerts
|

How science teachers' concerns about school‐based assessment of practical work vary with time: the Hong Kong experience

Abstract: School-based assessment of science students' practical skills has two important roles-as a complement to written papers in public examinations and as a catalyst for enriching the science curriculum in schools. This article describes a quantitative study of the concerns chemistry and biology teachers experience as they engage in the process of implementation of a school-based assessment scheme for practical work. A 23-item questionnaire was developed to measure five categories of teacher concern: evaluation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 6 publications
3
24
2
4
Order By: Relevance
“…Further, they did not agree that SBA can make the teaching an easier job. This is not a surprising finding and is in line with conclusions from previous studies (Cheung & Yip, 2004;Davison, 2007;Yip & Cheung, 2005). Although SBA is supposed to be an integral part of teaching and learning, many teachers seem to regard it as an extra burden.…”
Section: Descriptive Analyses On Tpb Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…Further, they did not agree that SBA can make the teaching an easier job. This is not a surprising finding and is in line with conclusions from previous studies (Cheung & Yip, 2004;Davison, 2007;Yip & Cheung, 2005). Although SBA is supposed to be an integral part of teaching and learning, many teachers seem to regard it as an extra burden.…”
Section: Descriptive Analyses On Tpb Componentssupporting
confidence: 91%
“…The Hong Kong Certificate of Education Examination (HKCEE) also included a component of SBA for many subjects since 1980. Despite the long history of SBA in Hong Kong, studies exploring teachers' views on SBA in HKALE or HKCEE (e.g., Cheung & Yip, 2004;Davison, 2007;Lam & Chan, 2010;Yip & Cheung, 2005) showed that teachers had many concerns about the implementation of SBA in terms of resources, workloads, and training. Not all were convinced regarding the reliability and validity of SBA.…”
Section: Introductionmentioning
confidence: 98%
“…The open-ended questionnaire developed by Hall & Hord (2001) was used to collect the seven teachers_ concerns about inquirybased laboratory work. The teachers were invited to respond to the openended question: FWhen you think about inquiry-based experiments in chemistry, what are your major concerns?_ Research by Cheung & Yip (2004) revealed that when teachers are confronted with an educational innovation, they may have five categories of concern:…”
Section: Methodsmentioning
confidence: 99%
“…One of the critical reasons is that teachers' concerns about the advocated innovations are not rightly observed and dealt with (Borgerding, Sadler & Koroly, ). The Stages of Concern (SoC) model (Cheung & Yip, , ; Hall & Hord, , ) is a useful framework for measuring teachers' concerns when they are in front of an EI, in terms of five categorical concerns— Evaluation , Information , Management , Consequence , and Refocusing . Employing the SoC framework, the present research aimed at probing into teachers' concerns about adopting VISOLE in formal curriculum teaching.…”
Section: Introductionmentioning
confidence: 99%